Islam di Belanda: Sejarah, Bahasa serta Fenomena Islamofobia - Umanah, Raidatul (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research aims to explore the history of Islam's arrival in the Netherlands, its subsequent development, and the global spread of Islamophobia, a phenomenon that has caused concern for the Muslim community. This research employs a qualitative approach, utilizing a library study method and a historical perspective. The data for this study was gathered from diverse literary sources from a range of journals, books, and news outlets. The study's findings revealed that Indonesians were the first immigrants to settle in the Netherlands, arriving around 1945. The life of the Muslim community in the Netherlands is dynamic, and its growth rate has been irresponsible, particularly among Native Dutch youth, such as students, who have studied Islam extensively. This is due to the perception that Islam is a religion that promotes terrorism and legalizes murder. Anti-Islamic causes, both domestically and internationally, contribute significantly to people's misconceptions about the origins of Islamic phobias, exemplified by the September 11, 2001, case in the United States.